2014
DOI: 10.1186/1471-2407-14-604
|View full text |Cite
|
Sign up to set email alerts
|

High nuclear expression levels of histone-modifying enzymes LSD1, HDAC2 and SIRT1 in tumor cells correlate with decreased survival and increased relapse in breast cancer patients

Abstract: BackgroundBreast cancer is a heterogeneous disease with a highly variable clinical outcome in which both genetic and epigenetic changes have critical roles. We investigated tumor expression levels of histone-modifying enzymes LSD1, HDAC2 and SIRT1 in relation with patient survival and tumor relapse in a retrospective cohort of 460 breast cancer patients. Additionally, we correlated expression levels with tumor differentiation and tumor cell proliferation.MethodsImmunohistochemical staining for LSD1, HDAC2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 26 publications
3
39
1
Order By: Relevance
“…These findings suggested that HDAC2 may be involved in the malignancy of breast cancer. Many reports have correlated HDAC2 expression with poor clinical outcome in patients with breast cancer (21,32). However, our data do not fully agree with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…These findings suggested that HDAC2 may be involved in the malignancy of breast cancer. Many reports have correlated HDAC2 expression with poor clinical outcome in patients with breast cancer (21,32). However, our data do not fully agree with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…KDM1A expression was also identified as an independent prognosticator of a few cancers. It has been reported that elevated expression of KDM1A is associated with poor prognosis in cancers [24,26,54,55]. Our data also identified the prognostic role of KDM1A in two independent cohorts of oral cancer.…”
Section: Discussionsupporting
confidence: 81%
“…All the 9 tumor cell lines were picked up from diversity cancers and all of the cells had been demonstrated to bear a high expression level of LSD1. 15,17,18 As shown in Table 4, compounds 5a and 5n treatment resulted in significantly cell viability inhibition with the IC 50 values ranging from 200nM to 3µM. Among these cancer cell lines, A549, H1299, A2780, HCT116, MCF-7,MDA-MB-231 and DU145 were sensitive to compound 5a with IC 50 < 1 µM and A549,H1299, A2780, HCT116,MCF-7, MDA-MB-231, PC-3 and DU145 were sensitive to compound 5n with IC 50 < 1 µM.…”
Section: Scheme 1 Initial Lsd1 Inhibitorsmentioning
confidence: 98%